(untitled) - Lindsay, Freda; (1914-2010) (U.S.A, 1984)
In (3z(BFreda: The widow who took up the mantle(3y(B, the author continues the chronicle of how God moved in her life in the intervening years. A woman of strength, courage and vision, Freda Lindsay was also a woman with a singular purpose in life $1! = (Bthat everything she did might bring glory and honor to the Lord she serves with whole-hearted dedication and total commitment.s
Keywords: Pentecostalism -- Biography